The State of Behavior Change Techniques in Virtual Reality Rehabilitation of Neurologic Populations - Felsberg, Danielle T.; Maher, Jaclyn P.; Rhea, Christopher K. (Frontiers in Psychology, 2019)
Background: Neurologic rehabilitation aims to restore function, address barriers to activity, and improve quality of life in those with injury to the nervous system. Virtual reality (VR) has emerged as a useful tool to enhance neurorehabilitation interventions and outcomes. However, the manner in which VR-based neurorehabilitation has been manipulated to optimize outcomes using theory-based frameworks has not been documented. Behavior Change Techniques (BCTs) are described as the smallest active ingredient in an intervention aimed to change behavior via theoretically-proposed pathways. The purpose of this review was to investigate the ways VR is being used in neurorehabilitation to improve upright mobility, and systematically code the VR interventions for active BCTs. Methods: Keyword searches were performed using database searches of SPORTDiscus, psycINFO, and PubMed. The search yielded 32 studies for inclusion. Coding for BCTs was conducted using the Behavior Change Techniques Taxonomy v1 (BCTTv1). Behavioral Practice, Graded Tasks, Biofeedback, and Explicit Feedback were the most commonly used BCTs. Results: All studies reported improvements in motor performance outcomes. However, none of the studies investigated the efficacy of each component of their VR intervention making it difficult to point to the most effective components of VR interventions overall. Conclusions: This review suggests that investigation into the specific components of VR interventions, along with purposeful implementation and reporting of BCTs will help improve understanding of the efficacy of VR as a neurorehabilitation tool. Future research could benefit from incorporating BCTs into the design process of VR interventions to produce optimal rehabilitation potential.